PERLINDUNGAN KONSUMEN TERHADAP TRANSAKSI DALAM SOCIAL-COMMERCE DI INDONESIA - Hanifah Noor Asufie; Lena Hanifah (LPPM STIH Awang Long, 2024)
The purpose of this research is to analyze consumer protection against transactions that occur on social-commerce platforms in Indonesia, which are reviewed from the legal relationship between business actors, consumers, and social-commerce platforms (TikTok Shop and Instagram Shopping) and to analyze electronic transactions on social-commerce electronic systems. whether it has fulfilled the principles of consumer safety and security. The type of research used by the author is a normative legal research type. The approach in this research uses the Statute Approach and a Conceptual Approach. The results of the research obtained that the legal relationship that exists on TikTok Shop is TikTok Shop as a third party that bridges the buying and selling transactions carried out by business actors and consumers. Meanwhile, in Instagram Shopping, the legal relationship that exists is between business actors and consumers, the role of Instagram Shopping is only as a page for business actors and consumers to meet. TikTok Shop and Instagram Shopping have several weaknesses in protecting consumer safety and security in carrying out transaction activities in their applications.